Subclinical Neurocognitive Dysfunction After Carotid Endarterectomy—The Impact of Shunting - Mazul-Sunko, Branka (Array, 2010)
Subclinical neurocognitive deficit after carotid endarterectomy (CEA) has been reported in 25% of patients.The influence of the type of anesthesia and shunting on early postoperative neurocognitive function remains unclear. Therefore, we analyzed the cognitive function after CEA using a battery of psychometric tests before surgery and on the first postoperative day. Twenty nine patients under regional and 28 under general anesthesia were included in the study. Regional anesthesia was administered creating a superficial cervical block, and the general anesthesia was induced using a standardized AQ3 manner. Then cognitive function was tested using a battery of psychometric tests before and 24 hours after surgery. S 100 b was determined at the same time points. A statistical difference was found between the results of the testing before and after CEA: decline in digit symbol test (9%), perceptual speed (6%), and spatial working memory (44%) and improvement in verbal fluency (6%) and attention (5%). The only intraoperative factor that correlated with the cognitive dysfunction was shunt insertion ; patients with a shunt had a lower perceptual speed (P=0.005) and worse spatial working memory (P=0.004). No correlation was found between the type of anesthesia or S 100 b level and any psychometric test, but these results might be influenced by the small sample size in our study. Shunt insertion was the only parameter correlated with cognitive decline on the first day after CEA. Regional anesthesia might offer indirect benefit because of a reduced need AQ4 of shunting in wakeful patients. Larger studies are required to clarify the role of shunting and type of anesthesia in early neurocognitive deficit after CEA and its impact on the quality of life.